Cabaran Melakar Profil Psikologi dan Psikiatri Ahli Kumpulan Pengganas Jemaah Islamiah : satu Kajian Kepustakaan - Yue Yunn, Goh; Yoke Yong, Chen (Jabatan Integriti & Pematuhan Standard Polis Diraja Malaysia, 2022)
This paper reviewed psychological and psychiatric profile of Jemaah Islamiyah. Results showed nit much development in profiling religion terrorist such as Jemaah Islamiah but radicalisation. Challenges in terrorist psychological and psychiatric profiling included lack of first hand informatio, subtle definition, low reliability and validity exist. Perhaps multidisciplinary profiling can assist Royal Malaysia Police (RMP) in the effort of counter terrorism